Advancing green entrepreneurship through Industry 4.0 technologies: An analysis of sustainable manufacturing and logistics optimization - Kulova Ivelina; Nikolova-Alexieva Valentina; Peev Kostadin (BIO Web of Conferences, 2024)
The study explores the role of Industry 4.0 technologies in fostering green entrepreneurship. It examines the integration of advanced technologies such as artificial intelligence (AI), machine learning, the Industrial Internet of Things (IIoT), and robotics into manufacturing processes. The primary goal of the study is to assess how these technologies can enhance production sustainability, optimize supply chains, and reduce the environmental footprint of logistics. The study employs a qualitative analysis of existing literature, case studies, and statistical data, providing a comprehensive assessment of the impact of these technologies on sustainable manufacturing and green entrepreneurship. The results indicate that Industry 4.0 technologies significantly contribute to sustainable manufacturing by reducing waste and improving energy efficiency. Despite the significant benefits, challenges such as high initial costs for smart equipment, the need for reliable data networks, and increased customer demands hinder the widespread adoption of these technologies. Industry 4.0 technologies offer unprecedented opportunities for enhancing sustainability and supporting green entrepreneurship. Realizing these opportunities requires collaborative efforts among businesses, governments, and stakeholders to ensure balanced economic development and environmental conservation.